2011
DOI: 10.1016/j.annemergmed.2011.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Will Patients “Opt In” to Perform Their Own Rapid HIV Test in the Emergency Department?

Abstract: Objective To evaluate the feasibility and accuracy of existing point-of-care (POC) HIV tests performed by an untrained patient compared to the routinely used HIV POC test offered to patients in two urban emergency departments (ED). Methods From April 2008 through December 2009, patients, who had completed a standard HIV oral fluid test performed by a trained healthcare professional and who were unaware of their results, were recruited to perform a rapid POC HIV test. Patients were given a choice of the oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
97
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(111 citation statements)
references
References 13 publications
11
97
2
1
Order By: Relevance
“…A review of 11 studies across different contexts suggested HIVST has high acceptability in most instances and increases the reach of HIV testing services with users capable of providing accurate results [3]. Data indicating user preference for oral or blood rapid tests are weak; however, users generally have more difficulty performing blood-based rapid tests [4,5]. In Singapore, of 350 participants using fingerstick rapid tests, almost 90 % found the kit and instructions easy to use and understand.…”
Section: Introductionmentioning
confidence: 99%
“…A review of 11 studies across different contexts suggested HIVST has high acceptability in most instances and increases the reach of HIV testing services with users capable of providing accurate results [3]. Data indicating user preference for oral or blood rapid tests are weak; however, users generally have more difficulty performing blood-based rapid tests [4,5]. In Singapore, of 350 participants using fingerstick rapid tests, almost 90 % found the kit and instructions easy to use and understand.…”
Section: Introductionmentioning
confidence: 99%
“…Pant Pai (2013) (9) Overall acceptability: 74% to 96% for both supervised and unsupervised settings (7,35,(43)(44)(45)(46)(47)(48)(49) (10,54,69) Overall: 47% to 100% (all US studies) (20,54,55,65).…”
Section: Linkage To Carementioning
confidence: 99%
“…In 2008, the license was amended to include the INSTI™ HIV-1/HIV-2 Antibody Test (6). This test is a preliminary antibody screening test that can be performed on site where the patient can receive their results immediately (< 1hr) (7)(8)(9)(10). If the patient receives a preliminary reactive result, a confirmatory test using traditional laboratory-based testing is required.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals should be able to follow clear instructions, properly collect their own samples, to accurately perform and interpret the tests [2]. Reported errors range from touching the pad of the test with fingers, to forgetting to place the test device in the developer for 20 min [7][8][9]12]. These can be reduced with clear instructions, in several different formats, languages to help reduce their occurrence [2].…”
Section: Test Conduct Performance and Interpretationmentioning
confidence: 99%
“…Current evidence from studies suggests a high acceptability of self-testing in most at risk for HIV populations worldwide, -like healthcare workers (HCWs) [6], men who have sex with men (MSMs) [7], emergency department attendees (EDAs) and the general populations from both developed and developing settings [8,9]. Despite strong evidence of acceptability, and preferences, challenges and opportunities, self-testing presents with its share of challenges and opportunities.…”
Section: Introductionmentioning
confidence: 99%